The Perfect Blend of Legendary Plot and Realistic Details — Jack London's Love of Life - qizi, Kenjayeva Vazira Akbarjon; Pirmanovna, Nazarova Gulbahor (International Journal on Integrated Education, 2023)
Love of life is one of the agent works of American realist author Jack London, who employments nitty gritty depictions of mental and ideological exercises to layout a breathtaking picture feeling, e.g. within the unforgiving Canadian tundra, the hungry, the injured beat the limits of their lives and survive in extraordinary conditions, so that perusers can have an immersive perusing encounter. In this 10,000 - word novel, London put the hero into an amazingly troublesome and menacing living environment that's nearly withdrawn from reality as well as exceptionally point by point and reasonable points of interest to show a sensational and undulating travel of survival to perusers by the third individual story point of view.This paper will burrow into the one of a kind charm of Jack London's imaginative creation from two points of view: plot advancement and detail characterization.